Mobile Banking As A Communication Media For Banking Services At Bank BTN Bengkulu Branch - Robby Kurniawan; Sri Narti; Indria Indria (Penerbit Jurnal Indonesia, 2022)
This study aims to find out how mobile banking is a communication medium for banking services at Bank BTN Bengkulu Branch, using Lasswell theory in Kurniawan (2018:62) which consists of: Who (who is the communicator), say what (what message he states), in which channel (what channel/media is used), to whom (who is the communicant) and whit what effect (the expected effect). This research is a qualitative research with a descriptive design. Data collection techniques in this study are primary data and secondary data. The results show that Who (who is the communicator), the communicator in this study is a mobile banking application at Bank BTN Bengkulu Branch. Say What (what message it states), the message given by the mobile banking application in this study is in the form of sentences or words and numbers desired by customers as mobile banking users of Bank BTN Bengkulu Branch. In Which Channel (What channel/media is used), the media in this study is the media used by customers in the use of mobile banking at Bank BTN Bengkulu Branch, namely the andorid phone. To Whom (Who is the communicant), the communicant in this study is the customer of Bank BTN Bengkulu Branch. Whit What Effect (Expected Effect), the effect in this study is to direct the communicator (application) to communicate according to what the customer wants so that ongoing transactions through the mobile banking application can run successfully and successfully.